Carrier's liability under international maritime conventions and the uncitral draft convention on contracts for the international carriage of goods wholly or partly by sea - Tong-jiang, Su; Peng, Wang (Transport, 2009)
The UNCITRAL Draft Convention on Contracts for the International Carriage of Goods Wholly or Partly by Sea was approved on Thursday, 3 July 2008 and would then be presented to the General Assembly of the United Nations for endorsement later this year. Many innovative features contained in the Draft Convention fill the perceived gaps in existing transport regimes. Carrier's liability compared with international maritime conventions and the Draft Convention as well as China Maritime Code is discussed in the paper. It is pointed out that although the Draft Convention plays a very important role in the development of international private maritime law regime, the entry into the force of the Draft Convention is not optimistic.First published online: 27 Oct 2010